PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA SANGEH, KECAMATAN ABIANSEMAL, BALI - I Putu Indra Wira Pratama; I Nyoman Sukamara; Wahyudi Arimbawa (UNHI PRESS, 2022)
Tourism is a social phenomenon that is very complex and integrates all aspects of human life. This very high potential has not been fully developed and utilized to its full potential. Given the many potential and strategic roles of Sangeh Village, it can be developed as a Tourism Village area. The potential of existing tourism objects is a natural beauty and culture that can be preserved and developed as one of the attractions of tourism, so that Sangeh Village has good enough potential to be developed as tourism, in addition to improving the economy for the local community. The purpose of this study is to find out the shape and level of community participation in development in Sangeh Tourism Village, and to find out the factors that influence the level of community participation in Sangeh Tourism Village. This study uses qualitative research with a deductive approach and quantitative data support obtained through observation, interviews and questionnaires to village officials and community leaders in Sangeh Village. Data will be analyzed by descriptive statistical analysis method.Based on the data analysis carried out and concluded that the forms of community participation in the development of Sangeh Tourism Village are in the quite active category; the form of community participation in the development of Sangeh Tourism Village is at a false participation level; and the factors of age, sex, level of education and livelihood each have a relationship with the activeness of the community participating in the development of Sangeh Tourism Village